Red Hat RHCE 8 practice tests - Vugt, Sander van (Pearson IT Certification, 2020)
Red Hat RHCE 8 Practice Tests provides three full practice exams so you can test your skills before taking the RHCE exam. This title was created by Sander van Vugt to support the Red Hat Certified Engineer (RHCE) Complete Video Course, 3rd Edition and is an essential part of preparing for the exam. It is suggested that you take these exams after watching Red Hat Certified Engineer (RHCE) Complete Video Course, 3rd Edition and/or attending Sander van Vugt's Red Hat Certified Engineer (RHCE) Crash Course through O'Reilly's Live Training program.